STUDY OF THE ROLE OF GENDER IN ISLAMIC EDUCATION PERSPECTIVE OF FEMALE SCHOLARS - Fitriyah, Ulfa; Muhid, Abdul (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This research examines female scholars globally and female scholars in Indonesia by examining the role of female scholars, aiming to analyze the role of female scholars in Islamic education, gender in Islamic education from the perspective of female scholars, and the contribution of female scholars in Islamic education. This research uses qualitative research techniques with a literature study approach (library research). Based on the findings from the review of scientific literature, female scholars in Islamic educational institutions have an important role as interpreters of religious texts but also as agents of social change by creating educational strategies that liberate, empower, concentrate on the needs of women, and develop curriculum with a gender justice perspective. Women scholars have succeeded in creating inclusive alternative plans and changing educational methods based on gender justice values despite some obstacles. Women clerics' intellect and spirituality are foundations for developing a contextualized Islamic education system. Intellectual contributions through writing and community engagement also expand Islamic education and gender equality to inspire generations of women in leadership.